Median ulnar nerves communication in the forearm: a study with autopsy material - Ballesteros, Luis; Forero, Pedro; Quintero, Iván (Italian Journal of Anatomy and Embryology, 2015)
The incidence of median-ulnar communication in the forearm presents variability in different population groups. The aim of this study was to determine the incidence and morphologic expression of the median-ulnar communication in a sample of the Colombian population. One hundred and eight forearms of autopsy material at the National Institute of Forensic Medicine of Bucaramanga, Colombia were studied. Using an approach of the flexor compartment of forearm the median and ulnar nerves were dissected and the communications between these two structures were characterized. The communicating branch occurred in 28 (25.9%) forearms. It occurred unilaterally in 12 specimens and bilaterally in 8, with statistically significant difference (P=0.01). The communication between the anterior interosseous and ulnar nerves was most frequent, observed in 13 (46.4%) forearms. The length of the communicating branch was 56.9±8.3 mm. The distance of the proximal and distal points of the communicating branch to the biepicondylar line was 59.6±15.4 mm and 102.7±23.5 mm respectively. The length of the forearm was 269.8±15.9 mm. A projection of the communicating branch from the upper third to the midthird of the forearm was observed. The incidence of the median-ulnar communication in the present study is in the high rank reported in the literature; there is an agreement with prior studies in finding more numerous communicating branches in the right forearm. The medianulnar communication should be taken into account for surgical approach of the forearm.